EKSTRAKSI PIGMEN ANTOSIANIN DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Lidya Simanjuntak, Chairina Sinaga, Fatimah (Universitas Sumatera Utara, 2014)
Extraction of anthocyanin pigments from the red pitaya’s peel (Hylocereus polyrhizus) has been done. Anthocyanin pigment from the red pitaya’s peel (Hylocereus polyrhizus) can be used as an alternative for sinthetys dye. Extraction of anthocyanin pigments in this experiment is using maceration method. There are three independent variables used in this experiment, they are the type of solvent (distilled water, 95% ethanol, ethyl acetate and 10% citric acid), solvent ratios (1:2, 1:3 and 1:4,) and the time of extraction process (1, 2 and 3 days). This experiment aims to determine the right type of solvent, better solvent ratio and better extraction time that used to get anthocyanin pigments from red pitaya’s peel. The measurements in this experiment are based on the pH value, the absorbance value and anthocyanin pigment yield. The experimental results shows that the levels of anthocyanin pigments of red pitaya’s peel dissolved in a solvent mixture of distilled water plus 10% citric acid produce the highest level of anthocyanin pigment yield is 62.68% at pH 2 and the extraction time are 3 days.